Role of core stability in biathlon shooting - Becker, J.; Cobb, T. (Journal of Biathlon Coaching, 2024)
What is core stability and how does it relate to shooting performance? Quick and accurate standing shooting is a critical factor in determining outcomes across a variety of race formats. Compared to prone shooting, hit rates are generally lower in standing shooting and penalty time following missed shots represents a greater percentage of overall race time. Standing shooting is also always performed last allowing minimal time to recover from any mistakes. Indeed, in race formats such as the pursuit standing shoot performance ranks second only behind starting position in determining overall race outcomes.